(untitled) (Journal of the College of Basic Education, 2025)
The aim of the current research is to evaluate the curriculum and teaching methods course at the College of Education in light of the requirements of comprehensive quality To achieve the research objective, the researcher adopted the descriptive approach as a study method. The research sample consisted of professors of the Curricula and Teaching Methods course at the College of Education, Al-Mustansiriya University, numbering (20) male and female instructors after excluding the exploratory sample. . The researcher prepared the research tool (questionnaire) in light of previous studies and literature and presented it to a group of experts and arbitrators. The researcher confirmed its validity and reliability. The number of its paragraphs reached (20) paragraphs that were distributed to the individuals of the research sample. After conducting the statistical analysis, the researcher reached a number of results, the most prominent of which is that the standards of comprehensive quality were not fully available in the teaching methods course, and that the content of the teaching methods course faces many weaknesses and shortcomings in several areas of it In light of the results reached by the researcher, the researcher concluded with a set of recommendations and proposals arising from the results of the study